Stiffness of Cell Micro-Environment Guides Long Term Cell Growth in Cell Seeded Collagen Microspheres - M, Shariatzadeh; CM, Perrault; D, Lacroix (Archives of Clinical and Biomedical Research, 2018)
Mesenchymal stem cells are widely implicated as a cell source for tissue engineering of skeletal tissue in cell-based therapy. Physical and mechanical cues are potent controlling factors in cell differentiation and can be implemented as a guide to study cellular response, matrix production and tissue regeneration. Microspheres were produced by gelation of bovine collagen type I with concentration of 2 mg/mL and 1,000-2,000 cells per droplet. Short and long term cell viability of human embryonic stem cell-derived mesenchymal progenitors (hES-MPs) and MG-63 osteoblastic cells as well as collagen microstructure and contraction were monitored during 28 days post encapsulation (pc). Results indicated that collagen concentration, hence mechanical properties of cell’s extracellular micro-environment are important in cell proliferation and differentiation. Contraction of cell-embedded microspheres was found to be vital in cell adaptation and the remodelling of their new environment. It was also found that collagen concentration of 2 mg/mL supports proliferation of hES-MPs while higher collagen concentration promoted the viability of MG-63s. Results of hES-MPs characterization in 3D soft environment and mechanically stimulated hES-MPs collagen microspheres can be used in cells/therapeutic carriers, implants in bone and cartilage healing applications. The microspheres developed in this study can also be used as a tool to build more optimised construct to transfer mechanically stimulated stem cells to the specific area of a defective bone which would add significant benefit to the field of bone regeneration.